Factors that influence employee retention among generation Y: the mediating role of employee recognition / Shafiq Shahruddin - Shahruddin, Shafiq (2019)
In the current complex business environment, organizations are facing challenges in retaining their employees, especially young employees that are known as Generation Y. The purpose of this research is to determine the factors that influence the retention of Generation Y employees in the banking sector. The study also seeks to provide the theory-based empirical evidence that the role of employee recognition mediate between the factors and retention of Generation Y employees. The study used Social Exchange Theory (SET) in order to explain the theoretical rationale of the factors, employee recognition and employee retention. A total of 302 bank employees representing a range of Malaysian banks in Klang Valley have been determined using stratified random sampling. PLS-SEM was utilized in order to explain the relationship among the factors towards employee retention as well as employee recognition as a mediator. The factors for employee retention in this research study are work environment, leadership, team and co-worker, training and career development, compensation, organizational policies and workplace well-being. The results had confirmed that compensation have influence and direct relationship toward the employee retention for Generation Y employees. Meanwhile, work environment, training and career development, organizational policies and workplace well-being had positive significant mediation effects on employee retention. Training and career development as well as workplace well-being have been identified to have full mediation effects, which means that these two constructs contribute significant relationship toward employee retention via employee recognition. Even though work environment and organization policies only illustrate as a partial mediation effects, however, these two constructs have been classified as complementary mediation effects. As a complementary mediation effects, employee retention in organizations have been enhanced among Generation Y employees, with the existence of employee recognition. The research study had undoubtedly provided in depth understanding that employee recognition plays an important role in retaining Generation Y employees in organizations. Besides that, the study had established that the factors that influence retention is part of recognition practice and program toward Generation Y and organizations can emphasize the value of employee recognition in their workplace practice.